Urinary excretion of duodenal purine derivatives in Kedah-Kelantan cattle - Pimpa, O; Liang, J.B; Jelan, Z.A; Abdullah, N (Elsevier, 2001)
Three male Kedah-Kelantan (KK) cattle each fitted with a ruminal and a T-shaped duodenal cannulae, with an initial body weight of 178.3 ± 5.78 kg were used to study the recovery rate of urinary purine derivatives (PD) after duodenal infusion of incremental amounts of purine bases (PB). During the experiment, the cattle were fed at a maintenance energy level with a diet containing 40% oil palm frond and 60% concentrates. Basal purine flows into the duodenum from the maintenance diet were estimated. Purine bases in the form of adenosine (46%) and guanosine (54%) were infused into the duodenum in four incremental rates equivalent to 10, 15, 30 and 45 mmol purine per day. Urinary allantoin, the principal PD was linearly correlated with PB input, while the contributions of other PD were not affected by treatments. The relationship between daily urinary PD (allantoin, uric acid, hypoxanthine and xanthine) excretion (mmol per day) and duodenal PB flow (mmol per day) was Y = 0.847X + 7.146 (r2 = 0.50, P < 0.001), suggesting that 0.85 of the supplied exogenous PB were excreted in urine, with an endogenous excretion of 7.15 mmol per day. Urinary PD excretion rates of zebu cattle are similar to those of European cattle.